URGENSI KOMUNIKASI MODEL STIMULUS ORGANISM RESPONSE (S-O-R) DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Andi Rahmat abidin; Mustika Abidin (IAIN Ambon, 2021)
Abstract: Communication in learning is a basic element that has a very urgent position and role in realizing the success of the educational process. Communication in learning can affect the achievement of the quality of education and of course can improve the quality of learning itself. The learning process cannot be separated from communication, therefore it is important for educators (teachers) to be skilled at communicating and understand the science and principles of effective communication in education, one of which is by applying the stimulus organism response model communication. In this paper, the author wants to analyze the urgency of the stimulus organism response (S-O-R) model of communication in improving the quality of learning. The author concludes that the communication of the stimulus organism response model is very important to be applied by the teacher because this communication is an action-reaction process so that verbal words, non-verbal cues, certain symbols will stimulate the communicant (students) to respond in a certain way. By implementing this communication, the message conveyed by the teacher can foster passion for the communicant so that the communicant quickly receives the message received and subsequently changes in knowledge, attitude and behavior so that this is an indicator of an increase in quality in learning.